Hubungan Motivasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Di PT. Batu Mas Sejahtera - Wahyu Ajie Setiawan; Marisi Aritonang; Anita Suharyani (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the relationship between work motivation and job satisfaction on employee performance at PT. Batu Mas Sejahtera. The research was conducted at PT. Batu Mas Sejahtera in Ketapang Regency. The sampling method used was simple random sampling, with a total sample of 60 respondents who are harvest employees. The data sources used in this study are primary and secondary data. The data analysis performed was Spearman rank correlation analysis. From the results of the data analysis, it can be concluded that motivation and job satisfaction have a moderate correlation with employee performance at PT. Batu Mas Sejahtera. The correlation of motivation and job satisfaction with employee performance is shown by the SPSS data processing results, which are 0.559 and 0.556, respectively.